Analysis of the Feeling of Online Learning in the Training of Teachers in Basic Education (Docentes 2.0 Journal, 2022)
During the health crisis, the Veracruzana Pedagogical University (UPV), as a teacher training institution in primary education, during the health crisis by COVID-19 established academic strategies for online, autonomous, and self-organized learning during the health crisis. The objective was to analyze students' feelings about their degree in primary education and their training in this modality. The research methodology was based on the experimental method, in the positivist paradigm, with a hybrid approach, non-experimental type, and descriptive design. The data collection tool provided a questionnaire with items on a Likert scale and was open to a sample of 3,306 subjects; all enrolled in February-July 2021. The results showed good acceptance of the pedagogical aspect and adaptation to remote work. However, the digital gap between the participants is notorious due to the localities where they live, since some are indigenous and rural, with Internet coverage challenging to access. Based on the above, no significant gender differences were found in the feelings expressed by the learners. Finally, although the training continued online, the students pointed out that face-to-face interaction is essential for learning socialization since it is not the same as interacting at a distance.
Keywords: Learning; appreciations; online education; pedagogy